2021
DOI: 10.1016/j.jadr.2021.100243
|View full text |Cite
|
Sign up to set email alerts
|

Depression during the COVID-19 pandemic amongst residents of homeless shelters in France

Abstract: Background Accumulating evidence suggests that the COVID-19 pandemic has negatively affected global mental health and well-being. However, the impact amongst homeless persons has not been fully evaluated. The ECHO study reports factors associated with depression amongst the homeless population living in shelters in France during the Spring of 2020. Methods Interview data were collected from 527 participants living in temporary and/or emergency accommodation following Fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 83 publications
1
25
2
Order By: Relevance
“…Based on the level of depression, most Indonesians in this study (71.7%) experienced symptoms of depression during the COVID-19 outbreak, the others experienced mild depression (28.5%), moderate depression (18.4%), and severe depression (24.8%). This prevalence is higher than that in a previous study conducted by Scarlett et al (2021) in France on people living in shelters, namely, 28% had mild depression, 17% had moderate depression, 10% had moderately severe depression, and 3% had severe depression. This high rate of depression may be due to unclear information about COVID-19.…”
Section: Discussioncontrasting
confidence: 67%
“…Based on the level of depression, most Indonesians in this study (71.7%) experienced symptoms of depression during the COVID-19 outbreak, the others experienced mild depression (28.5%), moderate depression (18.4%), and severe depression (24.8%). This prevalence is higher than that in a previous study conducted by Scarlett et al (2021) in France on people living in shelters, namely, 28% had mild depression, 17% had moderate depression, 10% had moderately severe depression, and 3% had severe depression. This high rate of depression may be due to unclear information about COVID-19.…”
Section: Discussioncontrasting
confidence: 67%
“…The health crisis had a significant psychological impact, aggravating emotional distress ( Yen-Hao Chu et al, 2020 ). Our study population reported unsatisfactory fulfilment of their basic needs (food, hygiene, accommodation) and high rates of mental disorders before being offered a shelter ( Vandentorren et al, 2016 , Scarlett et al, 2021 ). Similarly, the ApartTogether survey ( Spiritus-Beerden et al, 2021 ) highlighted that the mental health of refugees and migrants in Europe during the pandemic was significantly impacted, with increased levels of discrimination and daily life stressors.…”
Section: Strengths and Limits Of The Studymentioning
confidence: 84%
“…During this period, depression was also found to be associated with increased alcohol consumption in the general population [ 4 ]. Within the ECHO study sample, both waves showed rates of depression (30–31%) higher than national averages (∼20%) [ 79 ]. Serious mental disorders are known risk factors for homelessness, propagating the associated issues with employment and access to medical care and social support [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%